Bed-knob and broomstick - Norton, Mary.; Blegvad, Erik; Norton, Mary. (New York, NY Harcourt, 1957)
With the powers they acquire from a spinster who is studying to be a witch, three English children have a series of exciting and perilous adventures traveling on a flying bed that takes them to a London police station, a tropical island, and back in time to the seventeenth century.
A combined edition of 'The magic bed-knob' and 'Bonfires and broomsticks.'"
"Ages 8 and up"--cover p. [4].
Donation
Keywords: Magic -- Fiction; Space and time -- Fiction; Witches -- Fiction; England -- Fiction